THE ROLE OF ISLAMIC BANKING INSTITUTIONS IN SUSTAINABLE FINANCE AMIDST THE GLOBAL ESG TREND - Mutmainnah, Mutmainnah (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
ABSTRACT This article aims to systematically examine the contribution of Islamic banking institutions in supporting sustainable finance, particularly in the context of global developments related to Environmental, Social, and Governance (ESG) principles. The study also seeks to assess the extent to which Shariah values can be integrated with internationally adopted sustainability indicators.The method used in this research is a Systematic Literature Review (SLR), analyzing 30 scholarly articles published between 2015 and 2024. The selection and analysis process was conducted systematically, referring to the PRISMA protocol and thematic synthesis techniques to identify key findings.The results show that Islamic banks have significant potential in supporting sustainable finance, especially through the principles of Maqashid Shariah, which align with the ESG pillars. However, practical implementation of ESG in Islamic financial institutions still faces limitations, such as the lack of Shariah-based sustainability indicators, low transparency, and weak regulation and standardization. Moreover, a comprehensive and operational ESG-Maqashid integration model has not yet been developed at the institutional level.The study recommends the development of an integrative framework between ESG and Shariah principles to enhance the effectiveness of Islamic banks in contributing to sustainable development goals.Practically, this article is valuable for regulators, academics, and industry practitioners in developing Shariah-compliant financial policies and instruments aligned with ESG principles.Theoretically, it expands the horizon of Islamic economics research by proposing the incorporation of Islamic values into the global sustainability framework, which is increasingly relevant in the modern finance era